Pengaruh Kebijakan Fiskal Dan Kebijakan Moneter Terhadap Pertumbuhan Ekonomi Indonesia Periode Tahun 1975-2005 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract: This paper aimed to investigate the relationship between fiscal policy and monetary policy. In this paper, we considered not only fiscal policy and monetary policy but also the effect of overseas economy, which is reflected by exchange rate disequilibria from its natural rate. in capturing fiscal policy effect, we used government expenditure as a proxy, while monetary policy rule used in this paper pursue a non-full pledged monetary policy frameworks. Vector Autoregressive method was implemented in this paper as a tool in analyzing this relationship_ The data range is spread out from 1975-2005, which is obtained from International Financial Statistics (IFS). Estimation based on VAR method indicates that government expenditure alteration will have longer impact than the other two variables. In addition, the response based on this alteration is unstable. Meanwhile, monetary variable has the highest contribution among these variable in affecting output growth in Indonesia, This conclusion suggests that fiscal authority should reallocate its budget in productive sectors in order to raise output growth. However, both fiscal authority and monetary authority should also able to preserve output gap and exchange rate disequilibria in order to manage the economy fluctuation.